Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Di Pasar Alok Maumere - Maria Martina Mboko; Henrikus Herdi; Yoseph Darius Purnama Rangga (Populer: Jurnal Penelitian Mahasiswa, 2023)
The purpose of this research is to identify and analyze the factors that affect the income of traders in Alok Maumere Market. The analytical method used in this study is an associative-specific method with a quantitative approach. The sample in this study were 84 respondents. The data used are primary data and secondary data. Retrieval of data using observation, interviews, and questionnaires. While the data analysis technique is a multiple linear regression analysis technique. The results of this study indicate that capital has no effect on the income of traders in the Alok Maumere Market. While working hours have a positive and significant effect on the income of traders at the Alok Maumere Market. So it can be concluded that both positive and significant business capital and working hours have an effect on the income of traders at the Alok Maumere Market.